THE IMPACT OF ICT IMMERSION IN EDUCATIONAL TECHNOLOGY AND PEDAGOGICAL TECHNIQUES (International Journal of Food and Nutritional Sciences, 2022)
The impact of Information and Communication Technology (ICT) on education has always been widely discussed. The importance of incorporating ICT in education has also been mentioned in the National Education Policy (NEP) of 2020. Early theorists have discussed the theoretical basis for the need of ICT and the impact it can have in the teaching learning process. COVID-19 was a reason for accelerating the process of inclusion of ICT. Our society faces innumerable challenges with respect to access to education, high dropout rates etc. The researcher tries to look at how businesses or organisations can help in ICT immersion in various domains of teaching and STEM learning. The researcher intends to use qualitative techniques to research and discuss the same.